Diagnostic testing for and detection of physical abuse in infants with brief resolved unexplained events. (January 2023) - Doswell, Angela; Anderst, James; Tieder, Joel S.; Herman, Bruce E.; Hall, Matt; Wilkins, Victoria; Knochel, Miguel L.; Kaplan, Ron; Cohen, Adam; DeLaroche, Amy M.; Harper, Beth; Mittal, Manoj K.; et al.
Abstract: Background: A Brief Resolved Unexplained Event (BRUE) can be a sign of occult physical abuse. Objectives: To identify rates of diagnostic testing able to detect physical abuse (head imaging, skeletal survey, and liver transaminases) at BRUE presentation. The secondary objective was to estimate the rate of physical abuse diagnosed at initial BRUE presentation through 1 year of age. Participants and setting: Infants who presented with a BRUE at one of 15 academic or community hospitals were followed from initial BRUE presentation until 1 year of age for BRUE recurrence or revisits. Methods: This study was part of the BRUE Research and Quality Improvement Network, a multicenter retrospective cohort examining infants with BRUE. Generalized estimating equations assessed associations with performance of diagnostic testing (adjusted odds ratio (aOR)). Results: Of the 2036 infants presenting with a BRUE, 6.2 % underwent head imaging, 7.0 % skeletal survey, and 12.1 % liver transaminases. Infants were more likely to undergo skeletal survey if there were physical examination findings concerning for trauma (aOR 8.23, 95 % CI [1.92, 35.24], p  < 0.005) or concerning social history (aOR 1.89, 95 % CI [1.13, 3.16], p  = 0.015). There were 7 (0.3 %) infants diagnosed with physical abuse: one at BRUE presentation, one <3 days after BRUE presentation, and five >30 days after BRUE presentation. Conclusion: There were low rates of diagnostic testing and physical abuse identified in infants presenting with BRUE. Further study including standardized testing protocols is warranted to identify physical abuse in infants presenting with a BRUE. Highlights: Rates of diagnostic testing to detect physical abuse were low in infants with BRUE. Child physical abuse did not differ between lower- and higher-risk BRUE designations. The rate of physical abuse detected in infants with BRUE was low.